Comparison of Procalcitonin Versus C Reactive Protein in The Detection of Neonatal Sepsis - Ali, Wahid; Shirazi, Haider; Gul, Shireen; Halim, Alia; Ain, Qurat-ul; Zaman, Qaiser (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare procalcitonin and C-reactive protein in the detection of neonatal sepsis keeping blood culture as gold standard. Study Design: Cross sectional study. Place and Duration of Study: Neonatal Intensive Care Unit, Children Hospital, Pakistan Institute of Medical Sciences, Islamabad, from Jul to Dec 2018. Methodology: Neonates up to 28 days of age with the suspicion of sepsis were selected. All the patients with congenital malformation were excluded. Two bed-sided tests i.e., procalcitonin and C-reactive protein was performed using standardized laboratory methods. The diagnostic strength of both tests was compared. Results: A total of 154 neonates were enrolled in this study. Male neonates were dominant in this study 95 (61.7%). The mean age of patients was 6.1 ± 3.8 days. C reactive protein had a sensitivity and specificity of 50.9% and 28.7% respectively. While procalcitonin was found to have a comparatively high sensitivity and specificity 73.6% and 38.6% respectively. On blood culture test; klebsiella pneumoniae, pseudomonas, staphylococcus aureus were found out to be the most common pathogens. Conclusion: Procalcitonin has a better sensitivity and specificity than C reactive protein in the diagnosis of early neonatal sepsis.